Hubungan Perhatian Orang Tua dengan Kedisiplinan Kehadiran Siswa di Sekolah pada SMA Negeri 2 Amarasi - Kwangko, Milka Martina; Lohmay, Imanuel; Abel, Rizky M.; Lay, Andriyani E. (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
This study aims to find out: (1) a description of people's attention, (2) a description of student attendance discipline (3) the relationship between parental attention and student attendance discipline at SMA Negeri 2 Amarasi. This study uses a quantitative approach to the type of correlation research. The sampling technique was through Proportional Random Sampling with a total sample of 79 students. The data collection technique is the Parental Attention Questionnaire and the Student Attendance Discipline Questionnaire. Data analysis used descriptive analysis techniques and correlation analysis. The research results show that (1). Description of Parental Attention to SMA Negeri 2 Amarasi students belonging to the low category, if the low and very low categories are combined it becomes 60 students with a percentage of 76.0%. (2). Discipline of Student Attendance at SMA Negeri 2 Amarasi belongs to the low category, if the low and very low categories are combined it becomes 64 students with a percentage of 81.0%. (3) it is known that there is a significant relationship between the Parental Attention Relationship and Student Attendance Discipline of r-hit = 0.676 with a significance value of (sig) 0.000 < r-table (0.05) = 0.227. Thus it can be said that there is a correlation because rcount ≥ rtable, namely 0.676 ≥ 0.227. For this reason, there is a significant relationship between parental attention and student attendance discipline at SMA Negeri 2 Amarasi